COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.

Resorcinol-Azodianiline Covalent Organic Framework Supported FeOOH Quantum Dot-Catalyzed Electrochemical Ammonia Synthesis under Ambient Conditions - Shekhar, Pragalbh; Kosugi, Kento; Singh, Himan Dev; Kushwaha, Rinku; Rase, Deepak; Matsuzaki, Takumi; Jain, Chitvan; Singh, Piyush; Singh, Yashraj; Vinod, Chathakudath Prabhakaran; Kondo, Mio; Masaoka, Shigeyuki; et al. (CHEMISTRY OF MATERIALS, 2024)
Keywords: conversion; nitrogen; Recent Progress; reduction